Insulin Therapy is Associated With Increased Myocardial Interstitial Fibrosis and Cardiomyocyte Apoptosis in a Rodent Model of Experimental Diabetes - Adel, Fadi W.; Zheng, Ye; Wan, Siu-Hin; Greason, Christie; Pan, Shuchong; Ameenuddin, Syed; Chen, Horng H. (Frontiers in Physiology, 2022)
The incidence of diabetes mellitus (DM) is rising. DM is a risk factor for developing left ventricular (LV) dysfunction and adverse cardiovascular outcomes. Insulin, commonly used to treat DM, is associated with further worsening of such outcomes. Yet, the pathophysiology of the adverse properties of insulin on the heart remains poorly defined. Therefore, the objective of this study was to determine the biological effects of insulin on the heart in DM, which we tested in vivo in a diabetic rat model and in vitro on human cardiomyocytes and fibroblasts. Male Wistar rats were divided into 3 groups: controls (n=17), untreated diabetics (UDM, n=15), and insulin-treated diabetics (IDM, n=9). Diabetes was induced with Streptozotocin. Insulin pumps in IDM and saline pumps in UDM and controls were implanted for 4 weeks before tissue collection. Separately, cultures of human cardiomyocytes (AC16) and human cardiac fibroblasts (HCF) were treated with insulin to assess apoptosis and fibrosis, respectively. In rats, insulin partially rescued the DM-associated weight loss while fully restoring euglycemia. However, IDM had 2x the rate of LV fibrosis (p <0.0001) compared to UDM, and triple the rate of cardiomyocyte apoptosis compared to controls (p < 0.05). Similarly, in vitro, insulin triggered apoptosis in a dose-dependent fashion in AC16 cells, and it increased fibrosis and upregulated SMAD2 in HCF to levels comparable to Transforming Growth Factor Beta 1. Therefore, we conclude that insulin therapy is associated with increased cardiomyocyte apoptosis and myocardial interstitial fibrosis. Longer studies are needed to explore the long-term effects of insulin on cardiac structure and function.